Development of the Organizational Model for Organ Donation Coordination in Ukraine to Increase the Satisfaction of Patients’ Needs for Transplantation-Based Medical Care - D. M. Koval (Transplantation and artificial organs, 2025)
The article analyzes the current state of the transplantation system in Ukraine, identifies key organizational problems that limit the development of deceased organ donation, and substantiates the need to transform the existing model of transplantation activity coordination. It has been proven that the current system of organizing the identification of potential donors through contractual relationships between transplant centers and healthcare facilities creates prerequisites for conflicts of interest and violation of the principle of equal access of recipients to donor organs. Based on the analysis of the experience of European Union countries, particularly the Spanish transplantation model, it is proposed to create a regional network of coordination centers as structural units of the national transplant coordination institution. An organizational model has been developed that provides for the establishment regional centers with clearly defined functionality for monitoring potential donors, organizational and methodological support for the brain death diagnosis procedure, donor conditioning, communication with relatives of the deceased, and logistical support for the donation process. The economic efficiency of the proposed model is substantiated and the expected results of its implementation are determined, which include an increase in the level of deceased organ donation from 3,68 to 10–15 per 1 million population within three years, which will increase the level of satisfaction of patient needs for organ transplantation from 15% to 50–60%.